Prepubertal vaginal discharge: Vaginoscopy to rule out foreign body - Ekinci, Saniye; Karnak, İbrahim and Tanyel, Feridun Cahit and Çiftçi, Arbay Özden (The Turkish Journal of Pediatrics, 2016)
Medical records of all prepubertal patients who underwent vaginoscopy to rule out vaginal foreign body between 2004 and 2013 were reviewed retrospectively. All patients were evaluated by pediatricians prior to surgical consultation. Vaginoscopy is performed in the operating room under general anesthesia. During the study period, 20 girls with persistent vaginal discharge with a mean age of 6.8 years (1-13 years) underwent vaginoscopy to rule out vaginal foreign body. Six patients had bloody vaginal discharge and 4 had recurrent vaginal bleeding lasting for more than one month. Ten patients had purulent vaginal discharge lasting for 1-7 months. None of vaginal cultures revealed pathological bacteria or candida species. Preoperative imaging techniques revealed vaginal foreign body in one patient only. Vaginoscopy demonstrated vaginal foreign bodies in four patients. Foreign bodies were grass inflorescence, safety pin and undefined brownish particles (n=2), which may be pieces of toilet paper or feces. There was no complication related to vaginoscopy and removal of foreign body. Hymen integrity was preserved in all patients. Persistent or recurrent vaginal discharge in prepubertal girls should raise the suspect of vaginal foreign body. Continuous flow vaginoscopy is mandatory to detect and remove any vaginal foreign body. Early diagnosis would prevent complications secondary to long-standing foreign bodies.